Artificial intelligence based clinical data management systems: A review. (2017) - Gazali,; Kaur, Sandeep; Singh, Inderbir
Abstract: The clinical data management system is widely used to manage the data that is collected during the clinical trials. This system offers various comfortable methods via which the data can be collected, managed and stored easily for further use. The points regarding the clinical data management that are covered in this review article are the basic introduction covering the general aspects of the clinical data management system and various clinical data management softwares plus the use and the importance of case report forms in CDM and the data management procedures that are being followed up for the proper management of the data so that it is easily accessible by the personnel. Also, the use of various softwares in the clinical data management process has been discussed depicting how the softwares perform various functions to keep the data in a managed, secured and an accessible form. As an endpoint, various future challenges and options are considered which give a detailed idea about the growth of clinical data management in the Pharmaceutical Industry. Highlights: Detailed information on clinical data management. Information on Case report forms. Knowledge regarding paper based systems and electronic data based systems. Information on various softwares used in Clinical Data Management system.